An unusual cause of pulmonary hypertension: Mediastinal hydatid cyst - Hanae Ramdani (Elsevier, 2022)
Hydatid disease is a parasitic zoonosis prevalent in sheep-rearing areas. The lung is the second most commonly involved organ following the liver. Intra-thoracic and extra-pulmonary hydatid disease is rare and can affect the mediastinum, heart, diaphragm, pleura, and chest wall. Uncommon locations represent a diagnostic challenge. We report clinical and imaging manifestations of a compressive mediastinal hydatid cyst revealed by pulmonary hypertension. Radiologists must be familiar with the imaging features of hydatid disease and contemplate the diagnosis when facing atypical chest cystic lesions, especially in patients from endemic regions or with evidence of hydatidosis in a different anatomical location.